Variation of Elastic Stiffness Parameters of Granitic Rock during Loading in Uniaxial Compressive Test - Samad Narimani; Seyed Morteza Davarpanah; László Kovács; Balázs Vásárhelyi (Applied Mechanics, 2023)
Any rock mechanics’ design inherently involves determining the deformation characteristics of the rock material. The purpose of this study is to offer equations for calculating the values of bulk modulus (K), elasticity modulus (E), and rigidity modulus (G) throughout the loading of the sample until failure. Also, the Poisson’s ratio, which is characterized from the stress–strain curve, has a significant effect on the rigidity and bulk moduli. The results of a uniaxial compressive (UCS) test on granitic rocks from the Morágy (Hungary) radioactive waste reservoir site were gathered and examined for this purpose. The fluctuation of E, G, and K has been the subject of new linear and nonlinear connections. The proposed equations are parabolic in all of the scenarios for the Young’s modulus and shear modulus, the study indicates. Furthermore, the suggested equations for the bulk modulus in the secant, average, and tangent instances are also nonlinear. Moreover, we achieved correlations with a high determination factor for E, G, and K in three different scenarios: secant, tangent, and average. It is particularly intriguing to observe that the elastic stiffness parameters exhibit strong correlation in the results.